Biologically effective dose of flumioxazin and pyroxasulfone for control of multiple herbicide–resistant waterhemp (Amaranthus tuberculatus) in soybean. Issue 2 (20th March 2022) - Ferrier, James; Soltani, Nader; Hooker, David C.; Robinson, Darren E.; Sikkema, Peter H.
Abstract: Two studies were conducted to ascertain the biologically effective dose (BED) of flumioxazin and pyroxasulfone for multiple herbicide–resistant (MHR) waterhemp [ Amaranthus tuberculatus (Moq.) Sauer] control in soybean [ Glycine max (L.) Merr.] in southwestern Ontario, Canada, during 2016 and 2017. In the flumioxazin study, the predicted flumioxazin doses for 50%, 80%, and 90% MHR A. tuberculatus control were 19, 37, and 59 g ai ha −1 at 2 wk after application (WAA) and 31, 83, and 151 g ai ha −1, respectively, at 12 WAA. The predicted flumioxazin doses to cause 5% and 10% soybean injury were 129 and 404 g ai ha −1, respectively, at 2 wk after emergence (WAE), and the predicted flumioxazin doses to obtain 50%, 80%, and 95% of the weed-free control plot's yield were determined to be 3, 14, and 65 g ai ha −1, respectively. In the pyroxasulfone study, the predicted pyroxasulfone doses that provided 50%, 80%, and 90% MHR A. tuberculatus visible control were 25, 50, and 88 g ai ha −1 at 2 WAA and 41, 109, and 274 g ai ha −1 at 12 WAA, respectively. The dose of pyroxasulfone predicted for 80% reduction in MHR A. tuberculatus density was 117 g ai ha −1, and the doses of pyroxasulfone predicted for 80% and 90% reduction in A. tuberculatus biomass were 204 and 382 g ai ha −1, respectively. The predicted doses of pyroxasulfone that caused 5% and 10% injury in soybean at 2 WAE were 585 and 698 g ai ha −1, respectively. The predicted doses of pyroxasulfone required to obtain 50%, 80%, and 95% yield relative to the weed-free plots were 6, 24, and 112 g ai ha −1, respectively. Flumioxazin and pyroxasulfone applied preemergence at the appropriate doses provided early-season MHR A. tuberculatus control in soybean.